PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA PERAWAT DI UNIT PELAYANAN RAWAT INAP RSU ANDI MAKKASAU KOTA PAREPARE - Kusumaa, Dwiyana; Mahfudnurnajamuddin, Mahfudnurnajamuddin; Arfah, Aryati (Universitas Muhammadiyah Parepare, 2021)
This study aims to carefully examine the desired effect of typical workload and work stress on the effective performance of responsible nurses in the Inpatient Service Unit of the Andi Makkasau Hospital, Kota Parepare. This empirical research was carefully conducted for two typically completed typical months, namely February to March 2020. The specific population in that social study in common was all competent nurses in the Inpatient Service Unit of the Andi Makkasau Hospital, Kota Parepare. The active population typically consisted of 161 nurses with a selected sample of 62 nurses. The data analysis tool typically using SPPS. The published results typically showed that 1.) The characteristic work typically causes a direct and significant effect on the used capability of them in the Inpatient Service Unit of the Andi Makkasau Hospital, Kota Parepare, meaning that the increasing efforts to typically handle typical workloads will also increase the effective performance of practical nurses, 2.) Work stress causes a direct and significant effect on work. Nurses in the Inpatient Service Unit of the Andi Makkasau Hospital, Kota Parepare, meaning that the increasing efforts to deal severely with job stress will also increase the efficient performance of them, 3) Of the two independent variables used in obstinately determining the local level of nursey performance, it instantly turns out that work stress variables typically include a dominant influence on nurse performance. In the Inpatient Service Unit of the Andi Makkasau Hospital, Kota Parepare, because it typically has a beta value that is greater than the workload variable.